Penggunaan Sapaan Karaeng dan Daeng Dalam Masyarakat Kecamatan Rappocini Kota Makassar: Kajian Sosiolinguistik - Pardi; Syahruddin; Arifuddin (Pusat Riset dan Inovasi Nasional, 2023)
The aim of this research is to describe the greetings of Karaeng and Daeng in the community in Rappocini District, Makassar City. This type of research is a qualitative descriptive research which refers to three systematic stages (1) data collection stage, (2) data reduction stage, (3) data presentation stage, (4) conclusion drawing stage. The data in this study were in the form of conversations which were then transcribed into written form using data collection in the form of interviews and observations. Sources of data were obtained from three sources of community leaders in the Rappocini sub-district and various places that became observation locations. The results of the study show that regarding the greetings of Karaeng and Daeng namely, (1) the greetings of Karaeng and Daeng are the highest greetings for the Makassar ethnic area which are now in the Rappocini District. This greeting is also only pinned on certain people by looking at lineage and still having the royal blood of a Karaeng and Daeng, however, greetings that follow based on blood ties only apply in ancient times, different from now, this usage is considered common and is still remains the highest respectful greeting but the embedding is different because it refers to a religion that encourages mutual respect and appreciation so that one of the manifestations of this is to use the greeting to older people, (2) There has been a change in the mention of the greeting Karaeng and Daeng based on the situation and the location of the greeting.